SEMIOTIKA KARIKATUR PANDEMI COVID-19 MELALUI MEDIA DARING (ON LINE) DI PERANCIS - Mardi Adi Armin; Nafiatul Amalia (JURNAL ILMU BUDAYA, 2020)
This study investigates the caricature representations contained in online media regarding the French government's response to the Covid-19 Pandemic. Also examined the response of citizens to government policies, including religious and other professional society. This research was conducted to try to examine aspects of Corona pandemic reporting through online media because this issue has become a worldwide concern. Pandemic has caused many victims The response of the community is directly reflected in the caricature. by using the semiotic approach, we will get the meanings of the caricatures under study. The caricature is the data in this study. Caricature as data is divided into four: caricature of the government version, caricature of the community version, caricature of the professional version and caricature which is a critique of the Chinese government scientific method used is semiotics as a theory that can interpret the explicit and implicit meaning of an image. The results of the study found that the French Government remained criticized despite trying to handle the pandemic to the maximum. Also depicted a sense of optimism and pessimism of citizens facing disaster. Also found criticism of the Chinese Government that is not open to investigations of the origin of the virus.